Pertanian Berkelanjutan Berbasis Eduwisata di Kawasan Produksi Widuri Desa Wonokerto, Kabupaten Semarang - Fitriana Ashari; Fulia Aji Gustaman (Universitas Hamzanwadi, 2026)
Sustainable agriculture based on educational tourism in the Widuri Production Area of Wonokerto Village has emerged as a response to the need to integrate agricultural production, educational tourism, and community empowerment. The sustainability of this system depends on the strength of its technical aspects and program innovations. This study aims to examine the profile of sustainable agriculture based on educational tourism and to analyze the role of social capital that supports the sustainability of the system. This study employs a descriptive qualitative approach through in-depth interviews, observation, and documentation. Informants consist of area managers, farmers, and local residents selected via purposive sampling—that is, the selection of informants based on their involvement and knowledge regarding the phenomenon under study. Data analysis was conducted using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Widuri Production Area has developed a sustainable agricultural system integrated with edutourism activities through circular agricultural practices and commodity diversification. Participatory learning-based agro-edu-tourism activities foster capacity building, innovation, and farmers’ openness to new knowledge. The sustainability of this system is significantly influenced by the community’s social capital, reflected in close-knit social networks, mutually built trust, and collective norms internalized in daily life. These conditions enable coordination, stability, and efficiency in the management of the area. Thus, agro-edu-tourism in the Widuri Production Area serves as a model for sustainable community-based development, with social capital as its primary foundation and a strategy for strengthening the local economy.